Respuesta :

Answer:

Explanation:

Given:

To arrange the given expressions from least to greatest, we simplify them first.

For

[tex]\begin{gathered} 2^3-2^1\text{ } \\ \text{Simplify} \\ 2^3-2^1=\text{ 8-2 =6} \\ \end{gathered}[/tex]

For

[tex]\begin{gathered} 3^2 \\ \text{Simplify} \\ 3^2=\text{ 9} \end{gathered}[/tex]

For

[tex]\begin{gathered} 2^1+3^1 \\ \text{Simplify} \\ 2^1+3^1=2+3=5 \end{gathered}[/tex]

We can arrange now the expressions from the least to the greatest. Therefore,

[tex]undefined[/tex]